Experimentally quantifying the effect of nest-site depth on the predation risk and breeding success of Blue Tits. (1st August 2018) - Fokkema, Rienk W.; Ubels, Richard; Tinbergen, Joost M.
Abstract: Predation is a key factor in the nesting preferences of birds. Studies indicate that cavity-breeding birds prefer deeper nest sites, possibly because they are more safe from predation. We studied the Blue Tit ( Cyanistes caeruleus ), a cavity-breeding passerine, to test (1) whether nest-site depth affects breeding success and (2) whether potential effects of nest-site depth on breeding success are related to predation risk. We performed 2 experiments to separate effects of nest-box depth from potential effects of the quality of the breeding pair. In the first (free-choice) experiment, Blue Tits competed for scarce deep nest boxes that were provided well before nest-box choice, enabling an association between nest-box quality and bird quality. In the second (forced-choice) experiment, we randomly altered nest-box depth after Blue Tits had chosen a nest box, thus disconnecting the association between nest-box quality and bird quality. We found no evidence that the occurrence of signs of predation was related to nest-box depth. However, we did find clear positive effects of nest-box depth (1) on clutch size and hatching success throughout the study area and (2) on fledging success, the number of fledglings, and the overall probability of nest success, specifically in parts of the study area with high predation. We found no indication of independent effects of parental quality on breeding success. Parents also seemed to perceive the shallower boxes as more risky; in shallower boxes, nest thickness was decreased, irrespective of the local predation pressure during the free-choice experiment. Parents nesting in shallow boxes may have had lower breeding success because of (1) increased actual (but undetected) predation and (2) reduced reproductive investment by parents, based on the latter's experience with predation or an evolutionary response to past predation risk.